Phosphatidylcholine alteration identified using MALDI imaging MS in HBV-infected mouse livers and virus-mediated regeneration defects. - Eun-Sook Park; Jeong Hwa Lee; Ji Hye Hong; Yong Kwang Park; Joon Won Lee; Won-Jae Lee; Jae Won Lee; Kwang Pyo Kim; Kyun-Hwan Kim (PLoS ONE, 2014)
In this study, we investigated whether hepatitis B virus (HBV) causes the alteration of lipid metabolism and composition during acute infection and liver regeneration in a mouse model. The liver controls lipid biogenesis and bile acid homeostasis. Infection of HBV causes various liver diseases and impairs liver regeneration. As there are very few reports available in the literature on lipid alterations by HBV infection or HBV-mediated liver injury, we have analyzed phospholipids that have important roles in liver regeneration by using matrix-assisted laser desorption/ionization (MALDI)-imaging mass spectrometry (IMS) in the livers of HBV model mice. As a result, we identified different phosphatidylcholines (PCs) showing significant changes in their composition as well as cationized ion adduct formation in HBV-infected mouse livers which are associated with virus-mediated regeneration defects. To find the factor of altered PCs, the expression kinetics of enzymes was also examined that regulate PC biosynthesis during liver regeneration. It is noteworthy that the expression of choline-phosphate cytidylyltransferase A (PCYT1A) was significantly delayed in wild type HBV-expressing livers. Moreover, the amount of hepatic total PC was also significantly decreased in wt HBV-expressing mice. These results suggest that infection of HBV alters the composition of PCs which may involve in HBV-mediated regeneration defects and liver disease.